2018
DOI: 10.1111/jvim.15141
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of plasma total magnesium in a cohort of cats with azotemic chronic kidney disease

Abstract: BackgroundHypomagnesemia is associated with increased mortality and renal function decline in humans with chronic kidney disease (CKD). Magnesium is furthermore inversely associated with fibroblast growth factor 23 (FGF23), an important prognostic factor in CKD in cats. However, the prognostic significance of plasma magnesium in cats with CKD is unknown.ObjectivesTo explore associations of plasma total magnesium concentration (tMg) with plasma FGF23 concentration, all‐cause mortality, and disease progression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 76 publications
4
24
2
Order By: Relevance
“…A number of other factors have been associated with circulating FGF23 concentration. A study of cats with naturally occurring CKD observed an inverse association between plasma tMg concentration and FGF23 concentration, and it has been hypothesized that FGF23 has an effect on renal magnesium handling . In our study, tMg was not significantly different between cats with increased SDMA concentrations and those with normal SDMA concentrations, and no significant correlation was found between plasma FGF23 and tMg concentrations.…”
Section: Discussioncontrasting
confidence: 67%
“…A number of other factors have been associated with circulating FGF23 concentration. A study of cats with naturally occurring CKD observed an inverse association between plasma tMg concentration and FGF23 concentration, and it has been hypothesized that FGF23 has an effect on renal magnesium handling . In our study, tMg was not significantly different between cats with increased SDMA concentrations and those with normal SDMA concentrations, and no significant correlation was found between plasma FGF23 and tMg concentrations.…”
Section: Discussioncontrasting
confidence: 67%
“…DBA/2 mice regardless of their fetuin-A genotype had hypomagnesemia associated with elevated serum FGF23. Likewise, rats on magnesium-deficient diet had elevated serum FGF23 [50] and CKD cats had inverse association of serum Mg and FGF23 independent of serum phosphate [51]. Collectively these results suggest that serum FGF23 may be associated with hypomagnesemia in addition to the well-established association with hyperphosphatemia.…”
Section: Discussionmentioning
confidence: 75%
“…DBA/2 mice regardless of their fetuin-A genotype had hypomagnesemia associated with elevated serum FGF23. Likewise, rats on magnesium-deficient diet had elevated serum FGF23 [47] and CKD cats had inverse association of serum Mg and FGF23 independent of serum phosphate [48]. Collectively these results suggest that serum FGF23 may be associated with hypomagnesemia in addition to the well-established association with hyperphosphatemia and morbidity.…”
Section: Discussionmentioning
confidence: 76%